Exploring the Use of Virtual Reality in Enhancing STEM Education for Children - Ethan Blake; Liam Hunter (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Virtual reality (VR) is an emerging tool in education that allows students to interact with complex concepts in an immersive environment. This paper investigates the potential of VR in enhancing Science, Technology, Engineering, and Mathematics (STEM) education for children. By reviewing various case studies, the paper explores how VR applications are being used to make abstract STEM concepts more accessible and engaging. The study concludes that VR enhances conceptual understanding, problem-solving skills, and critical thinking among young learners.